TRANSLATING CONVERSATIONAL IMPLICATURES FROM ENGLISH TO INDONESIAN IN YOUTUBE VIDEO ENTITLED THE TEAM MEETING - Aldha Williyan; Dila Charisma (Universitas PGRI Semarang, 2021)
YouTube is not only a platform for entertaining the viewers. Nowadays, language learners can use videos on YouTube as a tool to learn many things dealing with language. One of the benefits of watching YouTube videos is that learners can comprehend pragmatic equivalence. Therefore, this study aims to analyze the English dialogue among the speakers in the YouTube video entitled The Team Meeting and its Indonesian subtitle to reveal the pragmatic equivalence. The analyzed pragmatic element is conversational implicatures. Additionally, the translation strategies used in Indonesian subtitles are also analyzed. To do this, the qualitative methodology, particularly textual analysis is used. With textual analysis, some steps in analyzing the data are needed. First, the English dialogue among the speakers and its Indonesian subtitle are transcribed. Second, translation strategies and pragmatic equivalence are analyzed. Lastly, the data are presented in form of paragraphs. The results show that the translation strategies can assist the English dialogue and its Indonesian subtitle to reach pragmatic equivalence. Borrowing words from English in Indonesian and the same basic structures between both languages generally contribute to this equivalence.